2011
DOI: 10.1103/physrevb.83.184202
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation in Li-doped KTaO3studied by kinetic Monte Carlo

Abstract: The dielectric properties of Li-doped KTaO 3 are studied by kinetic Monte Carlo, using a microscopic model derived from first-principles calculations. The method allows equilibrium and nonequilibrium simulations on very large time scales inaccessible by a molecular dynamics simulation and adequately reproduces most of the peculiar characteristics of the system: dielectric relaxation, evolving with increasing Li content of the temperature dependence of the dielectric permittivity (from single to double peaked).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Factors that affect the ferroelectric phase transition temperature of perovskite oxides A 0 B 0 O 3 have been extensively studied. [15][16][17][18][19][20][21][22][23][24][25][26] Taking PbTiO 3 and BaTiO 3 as examples, theoretical studies based on the first-principles calculations revealed that the hybridization between the Ti 3d states and O 2p states is essential to generation of the ferroelectric instability in both PbTiO 3 and BaTiO 3 , and that the interaction between the Pb 6s and O 2p states is covalent and crucial for the higher phase transition temperature of PbTiO 3 , 15,16) whereas the interaction between Ba and O is almost ionic for BaTiO 3 . 17) Experimental results showed that the tolerance factor t ¼ ðr…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that affect the ferroelectric phase transition temperature of perovskite oxides A 0 B 0 O 3 have been extensively studied. [15][16][17][18][19][20][21][22][23][24][25][26] Taking PbTiO 3 and BaTiO 3 as examples, theoretical studies based on the first-principles calculations revealed that the hybridization between the Ti 3d states and O 2p states is essential to generation of the ferroelectric instability in both PbTiO 3 and BaTiO 3 , and that the interaction between the Pb 6s and O 2p states is covalent and crucial for the higher phase transition temperature of PbTiO 3 , 15,16) whereas the interaction between Ba and O is almost ionic for BaTiO 3 . 17) Experimental results showed that the tolerance factor t ¼ ðr…”
Section: Resultsmentioning
confidence: 99%
“…It has been confirmed that an off-center occupation of dopant ions could induce an effective dipole around it and thus enhance the ferroelectricity of the solid solution. [20][21][22] It is considered that Ca 2þ ions in A = Ca solid solution are located in the off-center position and thus enhanced the ferroelectricity of the solid solutions, leading to a higher T C{T of A = Ca solid solution than that of A = Sr solid solution.…”
Section: Resultsmentioning
confidence: 99%
“…Our KMC code is similar to the one used in Ref. 20. Once the supercell constructed, the blocks are divided in two categories: (i) polar blocks, (ii) non-polar blocks.…”
Section: Parameters Of the Kmc Simulationsmentioning
confidence: 99%
“…16,17 Therefore, much attention has been paid to investigate the dielectric properties of KT induced by alien impurities. [18][19][20][21][22][23][24] However, compared with alien defects, the ubiquitous native point defects-oxygen vacancies (V O s) are widely known to be the "culprit" for various properties of perovskite oxides. 25 In particular, V O s are capable to induce a polarized state in KT due to lattice distortion, as reported in other perovskites.…”
Section: Introductionmentioning
confidence: 99%